2003
DOI: 10.1002/hrdq.1053
|View full text |Cite
|
Sign up to set email alerts
|

Stress audits as a precursor to stress management workshops: An evaluation of the process

Abstract: This study describes the stress audit process and how it can be effectively linked with stress management workshop development and delivery. Specifically, four stress audits and four workshops based on them were conducted within an organization. Reactions indicated that the stress audit is a valuable tool for trainers.In today' s ever-increasing push to do more with less, employees are reporting more on-the-job stress than ever before (Cartwright & Cooper, 1997). While stress management workshops have been one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…with that of other factors that previous research has identified as buffers of the negative effects of family incivility for alternative outcomes, such as emotional regulation (Bai et al, 2016) and core self-evaluation (Lim & Tai, 2014). Such research also could consider organizational resources, such as whether the organization adopts adequate stress management counseling (Ormond, Keown-Gerrard, & Kline, 2003) or implements supportive work-life balance measures (ten Brummelhuis & van der Lippe, 2010), and their influences.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…with that of other factors that previous research has identified as buffers of the negative effects of family incivility for alternative outcomes, such as emotional regulation (Bai et al, 2016) and core self-evaluation (Lim & Tai, 2014). Such research also could consider organizational resources, such as whether the organization adopts adequate stress management counseling (Ormond, Keown-Gerrard, & Kline, 2003) or implements supportive work-life balance measures (ten Brummelhuis & van der Lippe, 2010), and their influences.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The reason for introducing students to these levels of intervention is to give them a more sophisticated understanding of what can be done to create healthy workplaces. At least in the United States, organizations seem to be stuck in a paradigm of placing the burden on employees to cope with stressful work environments rather than engaging in interventions to improve the environment (Gilbreath, 2008a; Murphy, 1988; Ormond, Keown-Gerrard, & Kline, 2003).…”
Section: Learning Objective 5: Compare Interventions That Create Healmentioning
confidence: 99%
“…They generally are questionnaire-based, quantitative measurements of an array of psychosocial factors. Although their potential has been acknowledged in the HRD literature (e.g., Ormond, Keown-Gerrard, & Kline, 2003), review of the literature indicates that HRD professionals rarely conduct stress audits. That is unfortunate because HRD professionals-because of their familiarity with organizational development and their interest in removing barriers to effective job performance-arguably are best suited for conducting stress audits.…”
Section: Description and Rationalementioning
confidence: 99%
“…And tertiary interventions seek to repair the damage stress has caused (Williams & Cooper, 1999). Unfortunately, at least in the United States, secondary interventions are prevalent (Murphy, 1988;Ormond et al, 2003). When managers report that their employees are experiencing high job stress, a typical organizational response is to conduct stress-management seminars that teach coping methods such as deep breathing, relaxation, time management, and changing the way one thinks about stressors.…”
Section: Description and Rationalementioning
confidence: 99%